Analisis Kepuasan Siswa Kelas IX Sekolah Menengah Pertama Terhadap Pembelajaran Daring Mata Pelajaran PJOK Pada Masa Pandemi Covid-19 Kecamatan Purwanegara 2020 - Nanang Nurrohim (YLPK Mahardhika, 2020)
The background in this study is that students are lazy to take part in online learning because of difficult signals and do not have data packages for learning needs during the COVID-19 pandemic, therefore there is a need for a description of student satisfaction during the online network learning process. The purpose of this study was to determine the satisfaction of junior high school students with online learning in PJOK subjects during the COVID-19 pandemic in Purwanegara district. The research method used is descriptive quantitative research, using a survey method which is conducted online via google form. The sample in this study was class IX students of SMP Negeri Purwanegara District using the simple random sampling technique. Based on the results of the study, it was shown that the satisfaction level of grade IX junior high school students with online learning in PJOK subjects during the COVID-19 pandemic in Purwakarta was in the satisfied category by obtaining overall results with a percentage of 64%. From these results indicate that students are satisfied with the learning that is being carried out online. The conclusion of this study shows that student satisfaction has been achieved. The results of the descriptive analysis show that the level of student satisfaction has an average value of 64% and is included in the satisfied category in the online learning process. Student satisfaction is shown from the factors of adequate facilities and infrastructure, teaching materials used accordingly, learning media used accordingly, mastery of teacher material, accuracy in using methods and techniques, participant trust and discipline of schedules, student satisfaction has been achieved in interaction and communication skills. , as well as guiding students. This study was measured using 5 dimensions of satisfaction, namely: tangibles, reliability, responsiveness, assurance, and empathy. So any learning model as long as the five dimensions are met and the role of the teacher during learning takes place greatly affects the level of student satisfaction in learning online or online. Suggestions from this research are expected to continue to improve the quality of schools, both in terms of human resources, facilities and infrastructure to support various interests and potentials. Hopefully the cooperation and coordination between schools and students can be improved and maintained well in the future. Keywords: student satisfaction analysis, online learning, sports Abstrak Latar belakang pada penelitian ini adalah siswa yang malas mengikuti pembelajaran secara daring di karenakan sinyal yang susah dan tidak memiliki paket data untuk kebutuhan belajar selama pandemi COVID-19, oleh karena itu perlu adanya gambaran kepuasan siswa selama proses pembelajaran jaringan daring. Tujuan penelitian ini untuk mengetahui kepuasan siswa sekolah menengah pertama terhadap pembelajaran daring mata pelajaran PJOK pada masa pandemi COVID-19 sekecamatan Purwanegara.Metode penelitian yang digunakan yaitu penelitian kuantitatif deskriptif, dengan menggunakan metode survey yang di lakukan secara online melalui google form. Sampel dalam penelitian ini siswa kelas IX SMP Negeri Kecamatan Purwanegara dengan menggunakan teknik Simple Random Sampling. Berdasarkan hasil penelitian menunjukkan bahwa tingkat kepuasan siswa kelas IX sekolah menengah pertama terhadap pembelajaran daring mata pelajaran PJOK pada masa pandemi COVID-19 sekecamatan purwanegara masuk pada kategori puas dengan memperoleh hasil keseluruhan dengan persentase 64%. Dari hasil tersebut menunjukkan bahwa siswa merasa puas dengan pembelajaran yang di laukan secara daring. Simpulan penelitian ini menunjukan kepuasan siswa sudah tercapai. Hasil analisis deskriptif diperoleh bahwa tingkat kepuasan siswa memiliki nilai rata-rata sebesar 64% dan masuk pada kategori puas dalam proses pembelajaran daring. Kepuasan siswa di tunjukan dari faktor sarana dan prasarana yang memadai, bahan ajar yang digunakan sesuai, media pembelajaran yang digunakan sesuai, penguasaan materi guru, ketepatan penggunaan metode dan teknik, kepercayaan peserta dan kedisplinan akan jadwal, kepuasan siswa sudah tercapai dalam kemampuan interaksi dan komunikasi, serta membimbing siswa. Penelitian ini di ukur menggunakan 5 dimensi kepuasan yaitu: tangibles, reliability, responsiveness, assurance, dan emphaty. Maka model pembelajaran apapun selama kelima dimensi terpenuhi dan adanya peran guru selama pembelajaran berlangsung sangat mempengaruhi tingkat kepuasan siswa dalam belajar daring atau online. Saran dari penelitian ini diharapkan untuk terus meningkatkan kualitas sekolah, baik dari segi sumber daya manusia, sarana dan prasarana untuk penunjang berbagai minat dan potensi. Semoga kerjasama dan koordinasi antara sekolah dan siswa bisa di tingkatkan dan dijaga dengan baik untuk kedepannya. Kata kunci: analisa kepuasan siswa, pembelajaran daring, olahraga